Optical laser systems at the Linac Coherent Light Source. (21st April 2015) - Minitti, Michael P.; Robinson, Joseph S.; Coffee, Ryan N.; Edstrom, Steve; Gilevich, Sasha; Glownia, James M.; Granados, Eduardo; Hering, Philippe; Hoffmann, Matthias C.; Miahnahri, Alan; Milathianaki, Despina; Polzin, Wayne; et al.
<x xml:space="preserve">Abstract</x> Ultrafast optical lasers play an essential role in exploiting the unique capabilities of recently commissioned X‐ray free‐electron laser facilities such as the Linac Coherent Light Source (LCLS). Pump–probe experimental techniques reveal ultrafast dynamics in atomic and molecular processes and reveal new insights in chemistry, biology, material science and high‐energy‐density physics. This manuscript describes the laser systems and experimental methods that enable cutting‐edge optical laser/X‐ray pump–probe experiments to be performed at LCLS.